INTEGRATING ELECTRONIC PORTFOLIO ASSESSMENT IN THE TEACHING AND LEARNING OF DIFFERENTIAL EQUATIONS - Zainal Abidin, Azizan (2009)
The pen and paper assessment is widely used to measure students‟ cognitive abilities, but fails to measure their soft skills. The Engineering Accreditation Council (EAC) reported that communication skills top the list of the employers‟ rating of skills/qualities 2002. Educationists thus seek for alternative tools that could best measure cognitive, affective and psychomotor skills. Tertiary educational benchmarking standards now require variety and comprehensive assessment modes that are able to measure the so desired learning outcomes set by stakeholders. The objective of this paper is to discuss the findings of a case study conducted at Universiti Teknologi PETRONAS (UTP) in view of the integration of the e-portfolio as an alternative assessment method in the teaching and learning of Differential Equations (DE) course. For this paper, only one aspect is discussed; a questionnaire issued to obtain students‟ feedback on such integration. One hundred and ninety first semester UTP engineering students are involved. A one-group ex post facto research design is employed. Using a 4-by-4 model for e-portfolio development, and given a time frame of seven weeks, each group submits an electronic-portfolio or e-portfolio saved on a 700MB-CD. This pilot study conducted in UTP provides some intuition on e-portfolio evaluation and students‟ preference of the assessment approach.